A Discussion of the Practical and Theological Impacts of COVID-19 on Religious Worship, Events and Pilgrimage, from a Christian Perspective - Dowson, Ruth (The international journal of religious tourism and pilgrimage, 2020)
This article explores the impacts of the Covid-19 pandemic in 2020 on the worship services and events of Christian communities. Focusing on the UK in terms of practice, the research includes early pandemic examples from a range of Christian traditions and denominations, as well as relevant cases from other countries. The Christian church organisations considered range from the extensive world-wide reaches of the Roman Catholic Church, to international Protestant denominations such as the Anglican Communion, and to independent non-denominational groupings and local churches. This paper considers the ways in which churches are coming to terms with the impacts of this pervasive virus on the global community, and on their own congregations. At a time when all religious events were postponed or cancelled, many churches moved online for the delivery of daily and weekly worship services. Yet, some other events needfully persisted; this has especially been the case for funerals, as the number of people who have died from the virus continues to increase around the world. Governments have imposed new regulations that required immediate changes in religious practice, and the effects of these are discussed, giving examples. And it is not only religious practice that is changing - religious tourism has shut down, whilst pilgrimage seems to have morphed into a new creature, enabling pilgrims to continue in their journeying. These new pilgrimages may be physical or virtual, but they have been moderated by the limitations on travel, by social distancing and by self-isolation. Meanwhile, theology is not exempt from alteration. The virus continues to impact on central religious practices, such as receiving the Eucharist (Holy Communion), sharing the Peace, and the use of religious buildings, transforming the ways that the Christian faith is practiced. The suggested introduction of ticketing for services moves beyond theology to the continued Eventization of Faith in this new world.